An aggressive approach to hyperopia management: a method of maximum use of adaptive reserves intrinsic for the algorithms of natural refractive development - N. Yu. Kushnarevich (Российский офтальмологический журнал, 2018)
The article is devoted to the management of children hyperopia, focusing on two principal issues: 1) determining the maximum level of hyperopia (according to age and other factors) below which no correction is required, and above which correction is mandatory; 2) if correction is mandatory, which correction parameters are appropriate. A brief review of modern approaches to the solution of these issues by domestic and foreign schools of ophthalmology and optometry is given. Based on the generalization of the results of clinical studies, a threshold trajectory of the refraction genesis of children with hyperopia is constructed, which determines the probability of a normal course of emmetropization. A therapeutic trajectory of refraction genesis for children with moderate and high hyperopia with no signs of decompensation is theoretically determined. Presumably, managing the patients along the described therapeutic trajectory by means of correction tools may help achieve the maximum acceleration of emmetropization with relatively small risks of development of concomitant complications // Russian ophthalmological journal. 2017; 10 (2): 78-85. doi: 10.21516/2072-0076-2017-10-2-78-85.